La vigilancia de la salud de los trabajadores 12 años después - Esteban Buedo, Valentín; Gallo Fernández, Mariano; Guzmán Fernández, Asunción; García Gómez, Montserrat (Cuadernos de Relaciones Laborales, 2007)
Most, if not all the companies, have started some kind of prevention activity since the new regulation of occupational risk prevention was issued on 1996. However, difficulties have been detected in the implementation of the new model of health surveillance. The aim of this paper is to promote discussion and improvement of health surveillance by describing who is making health surveillance, what and how it is been done.